Estimation of soybean agronomic performance in climatic scenarios for Southern Brazil - Minuzzi, Rosandro Boligon (Revista Ceres, 2017)
The study aimed to analyze the agronomic performance of soybean cultivated in Southern Brazil, in climatic scenarios. Climatic data from three cities located in the main soybean producing regions of Paraná, Santa Catarina, and Rio Grande do Sul were used in the Aquacrop 4.0 software. Thus, it was possible to simulate cycle duration, yield, water use efficiency in productivity of evapotranspiration water (WUE), net irrigation requirement, and harvest index adjusted for different climatic scenarios based on short-term (2016-2035) and medium-term projections (2046-2065) of the RCP4.5 scenario of the Intergovernmental Panel on Climate Change. The soybean cycle duration tends to decrease when the locality is colder. Productivity and WUE should increase even if there is no irrigation requirement in future climate scenarios.